The Effect of Mind Mapping Method on Creative Thinking Skills of The Tenth-Grade Students on Linear Motion Material - Ghoziyah Shaf; Khaeruddin Khaeruddin; Abd. Haris (Jurnal Ilmiah Pendidikan Fisika, 2023)
This quantitative research seeks to examine the effect of mind mapping on the creative thinking skills of students in class X at SMA Negeri 1 Wajo. This research's population consisted of all X MIPA class students at SMA Negeri 1 Wajo, while 60 students were randomly sampled from two classes. Probability sampling with simple random sampling was used for sampling. The research instrument was an essay-based test of creative thinking skills. The queries were developed based on the aspects of creative thinking to be measured, namely fluency, flexibility, originality, and elaboration, which Gregory's validity test validated. The prerequisite test consisted of a normality test and a homogeneity test, and the t-test was used to examine the relationship between the mind-mapping method and students' creative thinking skills. The average score of the experimental group was 23.23, which was higher than the average score of the control group, which was 17.77 points. The results of hypothesis testing with the t-test obtained a t-value of 6.057, which was greater than r-table, which was 2.002 at a significant level of 0.05, so it is concluded that there is an effect of learning with the mind mapping method on the creative thinking skills of students of class X on linear motion material at SMA Negeri 1 Wajo. This research contributed encouragement of the use of the mind mapping method on linear motion material in high school physics learning and validated creative thinking skills test instruments on linear motion material.